The antihypertensive efficacy of Piper sarmentosum aqueous extract as compared to perindopril in spontaneously hypertensive rats - Hashim Fauzy, Fatimatuzzahra; Mohd Zainudin, Maizura; Ismawi, Hidayatul Radziah; FT Elshami, Taher (2019)
Aims/Objective: One of the impediments in overcoming hypertension is treatment failure caused by patient compliance in conventional medicine. Herbal remedies receive less defiance, and thus have been studied considerably. This study aimed to evaluate the efficacy of Piper sarmentosum aqueous extract (PSAE) in reducing blood pressure via endothelial dysfunction amelioration as compared to angiotensin-converting-enzyme (ACE) inhibitor, Perindopril. Methods: Blood pressure indices, level of mesenteric artery nitric oxide (NO) and endothelin1 (ET-1) were studied in four different groups (n=6) of spontaneously hypertensive rats (SHR) i.e. i) received distilled water, ii) 3 mg/kg Perindopril, iii) 500 mg/kg PSAE, and iv) a combination of 1.5 mg/kg Perindopril and 500 mg/kg PSAE. The rats were treated for 28 consecutive days, and blood pressure was measured weekly. NO and ET-1 level were analysed at the end of treatment period, after the rats were humanely sacrificed. Results: All three groups that received treatments have significantly lower systolic, diastolic, and mean arterial pressure (P<0.05), as well as higher NO level (P<0.05), and lower ET-1 level (P<0.05) as compared to the group receiving distilled water. However, rats that received Perindopril have the lowest systolic, diastolic, and mean arterial pressure, highest NO level, and lowest ET-1 level, followed by SHR treated by combined therapy and PSAE. Conclusion: Use of PSAE alone in once daily (OD) dose does not demonstrate better outcome than use of conventional Perindopril therapy in hypertensive subject. Further trials are imperative to fully establish the efficacy, tolerability, and possible adjuvant capacity of this potentially therapeutic agent.